The plain Janes - Castellucci, Cecil 1969- (Little, Brown and Company, 2020)
When Jane moves to the suburbs and thinks her life is over, she and three new friends form a club to make public art but are soon distracted by romance
"Includes the complete PLAIN Janes collection: 'The PLAIN Janes', 'Janes in Love', and 'Janes Attack back'" (Buchrückseite), "plus bonus content such as the evolution of the graphic novel and original cover sketches" (Impressum)
"'The Plain Janes' originally published in 2007 by DC Comics. 'Janes in Love' originally published in 2008 by DC Comics." (Impressum)
"With a foreword by Mariko Tamaki" (Cover)
Keywords: Graphic novels